Minimally Invasive Percutaneous Transpedicular Screw Fixation of Acute Thoracolumbar Fractures - Abdelaal Abdelbaky (Egyptian Spine Association, 2016)
Background Data: Percutaneous transpedicular fixation systems have become more frequently used as it allows the surgeon to achieve same goals as standard open surgery but in a less invasive manner by insertion of pedicle screws and pre-contoured rods through a stab incision and elimination of the need for excessive muscle dissection. Purpose: The aim of this study is to evaluate the outcome of percutaneous fixation of acute thoracolumbar fractures. Study Design: A retrospective study. Patients and Methods: Retrospective review of patients with acute thoracolumbar fractures without neurological deficit treated with percutaneous fixation from January 2011 to January 2015. Baseline data include patient’s demographics, operative data, mechanism of injury, fracture level and kyphotic angle. Pain was assessed using visual analogue scale and radiological outcome was assessed as the amount of kyphotic angle correction. Results: Seventeen patients with thoracolumbar fractures were included in this study, 14 patients were male and 3 were female. The mean age ofthe patients was 41 years. The mode of fracture was fall from height in 13 patients and motor car accident in 4 patients. The mean operative time was 110 minute. The average hospital stay was 3 days. The mean kyphotic angle improved from 24 degrees before surgery to 7 degrees after surgery. The mean VAS improved from 8.4 preoperatively to 1.8 postoperatively. Conclusion: Fluoroscopic guided percutaneous transpedicular screw fixation can provide a safe and effective treatment for acute thoracolumbar fractures with significant reduction in blood loss,postoperative pain and hospital stay. (2015ESJ103)